Further results on edge irregularity strength of graphs - Muhammad Imran; Adnan Aslam; Sohail Zafar; Waqas Nazeer (Indonesian Combinatorial Society (InaCombS), 2017)
A vertex k-labelling φ:V(G){1,2,…,k} is called irregular k-labeling of the graph G if for every two different edges e and f, there is w_φ(e)≠ w_φ(f); where the weight of an edge is given by e=xyE(G) is w_φ (xy)=φ(x)+φ(y). The minimum k for which the graph G has an edge irregular k-labelling is called edge irregularity strength of G, denoted by es(G). In the paper, we determine the exact value of the edge irregularity strength of caterpillars, n-star graphs, (n,t)-kite graphs, cycle chains and friendship graphs.",